A partial cpDNA trnL sequence from the extinct legume Streblorrhiza speciosa confirms its placement in the tribe Coluteae (Fabaceae) - Heenan, Peter B.; Wood, Jamie R.; Cole, Theresa L. (Phytotaxa, 2018)
We report a partial cpDNA trnL sequence of 203 base pairs from the extinct legume Streblorrhiza speciosa that was obtained from herbarium specimens collected from Phillip Island, south-western Pacific Ocean, in 1836. Bayesian phylogenetic analysis of the trnL sequence of S. speciosa and those of other Fabaceae species placed S. speciosa as a member of the tribe Coluteae, along with the Australian and New Zealand genera Carmichaelia, Clianthus, Montigena and Swainsona. Smaller genetic distances and shared morphological features indicate stronger links within this group may exist between S. speciosa and Carmichaelia.